EVALUATION OF THE USE OF ANTIMALARIA MEDICINES IN HANURA HEALTH CENTRE PESAWARAN DISTRICT PERIOD JANUARY-DECEMBER IN 2018 - Akhmad Rokiban; Ramadhan Triyandi; Karnila Sari (JFL : Jurnal Farmasi Lampung, 2020)
Abstract Malaria is a public health problem in Indonesia, especially those living in isolated areas. This is published in Presidential Regulation No. 5/2010 concerning the National Medium Term Development Plan for malaria endemic areas, which are divided into high, medium and low endemic areas. High endemic if the API is greater than 50 out of 1,000 population in the provinces of Maluku, Papua, North Sumatra and East Nusa Tenggara. Moderate endemic if the API is 1 to less than 50 dari 1,000 population in the provinces of Aceh, Bangka Belitung, Jambi and West Nusa Tenggara. Low endemic if the API is 0-1 per 1,000 population in Kalimantan, Sulawesi, and parts of Java. This study aims to determine the evaluation of the use of antimalarial drugs with the characteristics of age, sex, and type of malaria plasmodium at the Hanura Public Health Centre based on the criteria of the right indication, the right drug, the right dose, the right interval of drug administration (4T). This research is a descriptive research with purposive sampling method. Collection of prescription data and medical records in January-December 2018. The results showed that in cases of Malaria based on age, the most common cases occurred in the age range of 56-65 years, amounting to 99.6%, based on sex experienced in men by 77.41%, based on body weight the most occurred at 41-59 kg at 45.16%, based on the type of plasmodium experienced plasmodium vivax mostly at 84.95%. Based on these data, it was concluded that the evaluation of the use of antimalarial drugs based on 4T criteria was 100% accurate indication, 100% correct drug, 72.04% correct dose, 98.92% correct interval of drug administration. Keywords: Malaria vivax, treatment, Puskesmas, 4T